PENGARUH PEMBELAJARAN STAD BERBANTUAN BOOKLET ACCORDION MATERI SPU KELAS X SMA NEGERI 2 SINGKAWANG - Patia, Patia; Hairida, Hairida; Muharini, Rini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aims of this research is to know the difference of learning outcomes between learning process using cooperative model STAD type, assisted Booklet Accordion and using conventional model. This research used Quasi Experimental Design with Nonequivalent Control Group Design. The sampling technique used simple random sampling technique, where class X MIA 1 with 27 students as experiment class and class X MIA 3 with 30 students as control class. U Mann Whitney test was conducted to analys gain score data. The analysis result gave Asymp.sig (2-tailed) value 0.000 (sig <0,05), indicating that there were differences in learning outcomes between students who are given cooperative learning model STAD type assisted media booklet accordion and conventional methods. The effect size calculation showed that cooperative learning model STAD type assisted media booklet accordion gave influence toward learning outcomes class X MIA SMA Negeri 2 Singkawang on periodical system of element with 1,03 high category. Keywords: Cooperative, Student’s Achievements, Booklet Accordion